2015
DOI: 10.1590/1678-775720140122
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin expression in reactive lesions of gingiva

Abstract: Reactive proliferations of the gingiva comprise lesions such as pyogenic granuloma (PG), inflammatory fibroepithelial hyperplasia (IFH), peripheral ossifying fibroma (POF), and peripheral giant cell lesion. Osteopontin (OPN) has a dual role, it promotes mineralization when it is bound to solid substrate, and on the other hand, it inhibits mineralization when it is seen in association with solution.Objectives The study aimed to evaluate the expression of osteopontin in normal gingival tissue and different types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…), reactive gingival lesions (Elanagai et al. ), and other oral mucosal diseases (Danielsson et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…), reactive gingival lesions (Elanagai et al. ), and other oral mucosal diseases (Danielsson et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…OPN produced by osteoblasts at various stages of differentiation is one of the vital non-collagenous bone matrix proteins. High OPN calcium-binding potential can promote calcium adhesion, thus influencing mineralization events (42). Col-1, an early marker of osteogenic differentiation, is a major extracellular matrix component of periodontal tissues that promotes osteoblast differentiation and mineralization (43).…”
Section: Discussionmentioning
confidence: 99%
“…Also, formation and structure of the hard tissue in OF share more similarities with normal bone and cementum, and this could be another probable reason for higher expression of OPN in OF. Moreover, some studies demonstrated higher expression of OPN in peripheral OF compared to other reactive lesions which are not related initially to periodontal ligament [37,38]. Also, it could explain its overexpression in FD of the jaws compared to osteofibrous dysplasia, a FOS of long bones.…”
Section: Discussionmentioning
confidence: 99%